DIFFERENTIATED LEARNING PRODUCTS VIEWED FROM STUDENTS’ LEARNING STYLES: ITS IMPACT ON STUDENTS’ SPEAKING ABILITY - Nike Aprilia; Yunik Susanti; Diani Nurhajati (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
Speaking is one of the most important skills in learning English. There are many factors of the success in learning speaking, one of which is students' interest, motivation as well as teachers' learning methods. In the implementation of Merdeka Curriculum teachers have to consider to implement differentiated learning process in teaching learning process. This study aims to describe (1) the frequency of the student’s learning styles, (2) students speaking ability before and after being taught using differentiated products viewed from the student’s learning styles, and (3) the effect of differentiated products from the student’s learning styles to the tenth-grade students at SMKN 1 Kediri. This pre-experiment research used questionnaires, tests, and documentation to collect the data The results of the study showed that the students’ learning styles were grouped into 3 types (auditory, visual and kinesthetic) with 12 (37.5%) students were auditory styles; then 11 (34.4%) were visual styles; and 9 (28.1%) were kinesthetic learning style. The mean for the pre-test, was (42.63), classified as very poor, while the mean score for the post-test was (72.38), classified as good. The t-test computation showed that the t-score was greater than the t-table (-26.460>2.039) at a significance degree of 5% and at significant level of 0.000 is smaller than 0.05 (p<0.05). Thus, it can be concluded that differentiated learning products viewed from students’ learning style has significant effect to the students' speaking ability.